Frequency and risk of SARS-CoV-2 reinfections in Norway: a nation-wide study, February 2020 to January 2022 - Håkon Bøås; Margrethe Larsdatter Storm; German Tapia; Anja Bråthen Kristoffersen; Astrid Louise Løvlie; Ketil Størdal; Trude Marie Lyngstad; Karoline Bragstad; Olav Hungnes; Lamprini Veneti (BMC Public Health, 2024)
Abstract Background SARS-CoV-2 reinfection rates have been shown to vary depending on the circulating variant, vaccination status and background immunity, as well as the time interval used to identify reinfections. This study describes the frequency of SARS-CoV-2 reinfections in Norway using different time intervals and assesses potential factors that could impact the risk of reinfections during the different variant waves. Methods We used linked individual-level data from national registries to conduct a retrospective cohort study including all cases with a positive test for SARS-CoV-2 from February 2020 to January 2022. Time intervals of 30, 60, 90 or 180 days between positive tests were used to define potential reinfections. A multivariable Cox regression model was used to assess the risk of reinfection in terms of variants adjusting for vaccination status, demographic factors, and underlying comorbidities. Results The reinfection rate varied between 0.2%, 0.6% and 5.9% during the Alpha, Delta and early Omicron waves, respectively. In the multivariable model, younger age groups were associated with a higher risk of reinfection compared to older age groups, whereas vaccination was associated with protection against reinfection. Moreover, the risk of reinfection followed a pattern similar to risk of first infection. Individuals infected early in the pandemic had higher risk of reinfection than individuals infected in more recent waves. Conclusions Reinfections increased markedly during the Omicron wave. Younger individuals, and primary infections during earlier waves were associated with an increased reinfection risk compared to primary infections during more recent waves, whereas vaccination was a protective factor. Our results highlight the importance of age and post infection waning immunity and are relevant when evaluating vaccination polices.